Assessment of Environmental Contamination with Methicillin-Resistant Staphylococcus Aureus at Some Hospitals in Kerbala City, Iraq - Abdulrazaq Al-Khfaji, Zahraa; Saad Jalil, Bilal; Hatif Mahdi, Zahida (Kerbala Journal of Nursing and Health Sciences., 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the bacteria that causes hospital-acquired illnesses that is most resistant to antibiotics. The study aimed to examine the prevalence of MRSA in the environment of two hospitals in Kerbala city: Maternity Hospital (MH), and Kerbala Instructional Pediatric Hospital (KIPH) from (beds , Incubators of premature infants, floor, tables, walls, and Kitchenware) from October 2022 to December 2022 to identify the source of spread to develop appropriate control measures. The isolates were identified according to cultural, microscopic characteristics, biochemical tests, and Api-Staph system. The results showed that the floors and beds were the most contaminated sites in the wards of MH. The highest percentage of antibiotic resistance in MH and KIPH was to Kanamycin 88.8%, and Lomefloxacin 54.5%. The contamination in MH was due to the high numbers of pregnant women and it` companions thus the lack of time available to perform infection control program as well as lack of interest in the cleaning the tables in the KIPH making them as a source of survival and proliferation of MRSA. This study reveals widespread contamination of the hospitals environment, highlights the complexities of the problem of contamination, and conﬁrms the need for more-effective cleaning of the hospital environment to eliminate MRSA.